2001
DOI: 10.1111/j.1346-8138.2001.tb00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leiomyomatosis with Type 2 Segmental Involvement

Abstract: A 21-year-old man had histologically-confirmed diffuse cutaneous leiomyomatosis. The lesions showed a peculiar distribution in that they predominantly involved several segments of the right side of his body; in addition, less extensive, nonsegmental lesions were present on both sides of the body. Although this case was apparently sporadic, the genetic mechanism of loss of heterozygosity provides a plausible explanation for this unusual presentation. If the patient were heterozygous for the underlying mutation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Happle [8] proposes the distinction between type 1 segmental involvement, where the segmental lesions show the same severity as in the non-mosaic trait, and type 2 segmental manifestation, where the intensity of involvement observed in the circumscribed area is far more pronounced. There are several reports of cutaneous leiomyomatosis presenting with this type 2 segmental distribution [9,10,11,12]. Together with the above-mentioned hypothesis of a two-hit model of tumorigenesis, this strongly suggests that loss of heterozygosity at the FH locus in the involved skin is due to a second event occurring at a post-zygotic stage.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Happle [8] proposes the distinction between type 1 segmental involvement, where the segmental lesions show the same severity as in the non-mosaic trait, and type 2 segmental manifestation, where the intensity of involvement observed in the circumscribed area is far more pronounced. There are several reports of cutaneous leiomyomatosis presenting with this type 2 segmental distribution [9,10,11,12]. Together with the above-mentioned hypothesis of a two-hit model of tumorigenesis, this strongly suggests that loss of heterozygosity at the FH locus in the involved skin is due to a second event occurring at a post-zygotic stage.…”
Section: Introductionmentioning
confidence: 78%
“…Thus far, such extensive lateralized involvement has rather rarely been reported in genodermatoses showing a type 2 segmental manifestation [11,22]. If the family story is reliable, the hypothesis of a de novo heterozygous post-zygotic mutation with subsequent second mutational events is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, they present as brown-yellowish, red or skin coloured tumours which can reach into the subcutis. [1][2][3][5][6][7][8] The pathophysiology of segmental cutaneous leiomyomatosis is not fully known but new genetic aspects have arisen in recent years. Cutaneous leiomyomas usually emerge between the first and third decade of life preferentially on the proximal extremities, trunk and the face and neck region.…”
Section: Reportmentioning
confidence: 99%
“…[4][5][6][8][9][10] The combination of uterine and cutaneous leiomyomas is known as Reed's syndrome and recently the genetic alterations have been linked to chromosome 1q42.3-q43 (MCUL1). [4][5][6][8][9][10] The combination of uterine and cutaneous leiomyomas is known as Reed's syndrome and recently the genetic alterations have been linked to chromosome 1q42.3-q43 (MCUL1).…”
Section: Reportmentioning
confidence: 99%
“…[1] This results in pronounced lesions superimposed on the disseminated tumors of the ordinary phenotype. [5] Though the exact molecular etiopathogenesis of multiple cutaneous leiomyomas is not known, recent studies have demonstrated the involvement of a classical tumor suppressor gene encoding fumarate hydratase, in the pathogenesis of multiple leiomyomas. [1] The lesions are often sensitive to touch, cold, emotional stress, or spontaneous pain.…”
Section: Discussionmentioning
confidence: 99%